Technology of formation of readiness for employment of future teachers - Karaulov M. A. (Pedagogical experience: from theory to practice, 2022)
This article presents a technology for the formation of readiness for employment of future teachers, which includes stages (diagnostic, activity, reflexive-evaluative), content, professional motivation, professional intentions, professional identity, knowledge and skills associated with the employment process, reflexive-volitional qualities ), methods (training, dialogue, situational, game), forms (individual accompaniment, group).
Keywords: будущие педагоги; future teachers; готовность к трудоустройству; модель формирования готовности к трудоустройству; Readiness for employment; a model for the formation of readiness for employment